Sifat Industri, Pertumbuhan Perusahaan, dan Faktor Lainnya yang Mempengaruhi Fradulent Financial Statement - Anthony, William Henry; Lasar, Hilary Flora A. T. (Media Bisnis, 2024)
Abstract: This research was conduct to obtain empirical evidence regarding the factors that influence fraudulent financial statement actions. The factors studied are nature of industry, company growth, effectiveness supervision, quality of external auditors, director experience, external pressure, and change in auditor. Sampling in this study used purposive sapling which resulted in a sample of 166 companies originating from consumer cyclicals and consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The data obtained from the sample was analyzed using the logistic regression method in SPSS version 25. The result of this study show that nature of industry, company growth, and director experience has a positif effect on fraudulent financial statement, then external pressure has a negative effect on fraudulent financial statement, while effectiveness supervision, quality of external auditors, and change in auditor have no influence on fraudulent financial statement. Keywords: Fraudulent financial statement, nature of industry, company growth, effectiveness supervision, quality of external auditors, external pressure